PENGARUH TEMPERATUR TERHADAP SIFAT FISIK MEKANIK PADA SAMBUNGAN DIFUSI LOGAM TAK SEJENIS ANTARA SS400 DENGAN Al6061 - Hariyanto, Agus Hadi; Triyono, Triyono; Supriyanto, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Diffusion welding on the disimilar metal between steel SS400 and aluminum Al6061 by using induction furnace, the temperature variation and filler variation. Temperature variations that are used 850â°C, 875â°C and 900â°C. Filler that is used Fe and Cu powders, in variations filler Fe / Cu: 70/30%, 75/25%, 80/20%, on 30 minutes holding time. The results shows there is the presence of intermetallic layers in the temperaturs. Results of Scanning Electron Microscop (SEM), good diffusion process occurs on temperatures 850â°C and filler variations Fe: 75%, Cu: 25%. It occurs interface bonding steel and aluminum on diffusion area. Interface bonding steel and aluminum will produces intermetalic layer Fe2Al3. The results of good hardness distribution occurs on 900â°C filler variations Fe: 75%, Cu: 25%. It occurs intermetalic layer formation on diffusion area. Intermetalic layer formation is influenced by heat treatment and diffusion of Fe atoms and Cu atoms. The higher the heat treatment, the harder the Cu atoms. So it will affect the hardness intermetalic layer. By the higher heat treatment, the microstructure of the coating intermetalic will be so close. The more tightly layered arrangement intermatalic blistering effect on shear test. The results of tensile shear testing, high voltage value occurs on 900â°C filler variations Fe: 75%, Cu: 25%. It is influenced by a continuous heating process, thus causing the Cu atoms will be hard. With high heat, Fe atoms will diffuse to the base metal aluminum and copper atoms will diffuse to the base metal and Al6061 SS400. So that the Fe and Cu atoms will bond with the base metal that affects the mechanical properties.